2015
DOI: 10.1249/mss.0000000000000628
|View full text |Cite|
|
Sign up to set email alerts
|

Methods to Estimate V˙O2max upon Acute Hypoxia Exposure

Abstract: These data provide a robust quantitative framework for the curvilinear and interacting effects of altitude and baseline V˙O2max in determining an individual's effective V˙O2max at altitude. This predictive model is useful for a priori power calculations, design of future experimental studies, and prediction of aerobic capacity declines in applied settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
3
27
2
Order By: Relevance
“…Consistent with data on the dose-response effect of hypoxia on trueV˙O 2max (Bassett et al, 1999; MacInnis et al, 2015), we observed a curvilinear decrease in CP. Secondly, the effect of hypoxia on W′ appears to display threshold type characteristics since there were no significant changes at lower altitudes, whereas a decrease occurred at the highest altitude only (4,250 m).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with data on the dose-response effect of hypoxia on trueV˙O 2max (Bassett et al, 1999; MacInnis et al, 2015), we observed a curvilinear decrease in CP. Secondly, the effect of hypoxia on W′ appears to display threshold type characteristics since there were no significant changes at lower altitudes, whereas a decrease occurred at the highest altitude only (4,250 m).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have quantified the decrease in trueV˙O 2max that occurs at altitude (Bassett et al, 1999; Wehrlin and Hallén, 2006; Clark et al, 2007; MacInnis et al, 2015), however this is the first to examine the effect of altitude on CP and W′. Consistent with data on the dose-response effect of hypoxia on trueV˙O 2max (Bassett et al, 1999; MacInnis et al, 2015), we observed a curvilinear decrease in CP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, submaximal exercise endurance is clearly increased (22), as is the sense of well being and reduction of altitude illness. A recent meta-analysis of 80 studies, where altitude exposure was limited to 24 h, demonstrated that the decline in VO 2 max with altitude was greater for subjects with higher aerobic capacity (21). Their model predicts a 25% reduction from 1,600 to 4,350 m for subjects in this study, well above 15.5%.…”
Section: Discussionmentioning
confidence: 62%